Launching the partnership and assessing the challenges ahead: learning lessons year 1 and 2: forest partnership from Kalimantan districts to the global market place - Prasetyo, F.A.; Obidzinski, K.; Dermawan, A. (Center for International Forestry Research, 2007)
The Kalimantan Forest Partnership comes under the umbrella of the Asia Forest Partnership (AFP). It arose from a commitment made in 2002 at the World Summit in Johannesburg by the Netherlands’ Government to support the AFP’s efforts to promote sustainable forest management in Kalimantan, Indonesia. The Kalimantan activities are promoting collaboration among various parties and stakeholders, and linking improved forest governance in Kalimantan to international trade in Asia and Europe.This report details the lessons learned from the collaborative activities in Kalimantan. It also examines the current state of forest governance in Indonesia, the conversion of forest lands, and how international markets might influence Indonesia and Kalimantan’s forestry sector. The report also looks at the Kalimantan forest partnership’s response to regional problems, overviews its successes and analyzes its capacity building initiatives. The report also offers several recommendations for helping to ensure the partnership achieves its stated goal of “improved forest governance and sustainable forest management”.